Quassia undulata (Guill. &Perr.): Systematic Review - Ndiaye, Seyni; Diop, El Hadj Moussa; Ndiaye, Edouard Mbarick; Cisse, Mady; Ayessou, Nicolas C. M. (Discoveries in Agriculture and Food Sciences, 2025)
Forest trees are very important resources for living things. They are used in the daily life of human beings whether in the production of wood, in food, in medicine, in cosmetology… Among these forest resources, some are more exploited than others. These unconventional resources, however, hold enormous potential. This is how this document proposes to make the bibliographical review of the plant Quassia undulata. The research method used is the collection of information from scientific sites for downloading articles, books, and educational documents such as doctoral and master’s theses. The information obtained showed that Quassia undulata is used in traditional medicine as well as in modern medicine, especially in the treatment of malaria and cognitive diseases. The fruits are eaten and the seed oil is used in cosmetics and in the production of biodiesel. Its wood is highly prized and the seeds rich in quassinoids are used as a nematicide. However, in view of the many potentialities of the tree, it would be interesting to adopt means of preservation thus making it possible to preserve the important local know-how.